A Case Study of AOP and OOP Applied to Digital Hardware Design - Mück, Tiago R.; Gernoth, Michael; Schröder-Preikschat, Wolfgang; Fröhlich, Antônio A. (Proceedings of the 2011 Brazilian Symposium on Computing System Engineering (SBESC), 2011)
In this paper we explore a SystemC-based hardware design method which uses aspect-oriented programming concepts. We have designed a synthesizable resource scheduler at register transfer level by using only features available in the SystemC synthesizable subset. The results show that aspectoriented programming applied to digital hardware design provides a better separation of concerns at the cost of a negligible overhead. © 2011 IEEE.
UnivIS-Import:2015-04-16:Pub.2011.tech.IMMD.IMMD4.applyi
Keywords: Aspect-oriented programing; Digital hardware design; Reconfigurable hardware

Exzess: Hardware-based RAM encryption against physical memory disclosure - Würstlein, Alexander; Gernoth, Michael; Götzfried, Johannes; Müller, Tilo (29th International Conference on Architecture of Computing Systems, ARCS 2016, 2016)
The main memory of today’s computers contains lots of sensitive data, in particular from applications that have been used recently. As data within RAM is stored in cleartext, it is exposed to attackers with physical access to a system. In this paper we introduce Exzess, a hardware-based mitigation against physical memory disclosure attacks such as, for example, cold boot and DMA attacks. Our FPGA-based prototype with accompanying software components demonstrates the viability, security and performance of our novel approach for partial main memory encryption via memory proxies. The memory proxy approach will be compared to other existing mitigation techniques and possible further uses beyond encryption will be discussed, as well. Exzess effectively protects against physical attacks on main memory while being transparent to applications and the operating system after initializatio
Keywords: Memory disclosure; Memory encryption; Physical attacks

Implementierung und Vergleich verschiedener Strategien zur Durchführung von Ethernet Performance Messungen - Gernoth, Michael; et al. (Echtzeitsysteme im Alltag, 2006)
UnivIS-Import:2015-07-08:Pub.2006.tech.IMMD.IMMD4.implem